Unsteady mixed convection stagnation-point flow over a plate moving along the direction of flow impingement - Saleh, Siti Hidayah Muhad; Arifin, Norihan Md.; Nazar, Roslinda; Pop, Ioan (Emerald Group Publishing, 2017)
Purpose: The purpose of this paper is to present the results of an analysis performed to study unsteady mixed convection at the stagnation point flow over a plate moving along the direction of flow impingement. The similarity transformations are used to transform the governing nonlinear partial differential equation to a system of an ordinary differential equation. Design/methodology/approach: The transformed equations are then solved numerically by a shooting technique together with bvp4c function. Findings: The numerical results are compared with the corresponding results from previous researchers. The effects of the unsteadiness Parameter A, Prandtl number Pr, mixed convection parameter λ for plane (m = 0) and axisymmetric (m = 1) flow on the shear stress or the skin friction and heat transfer coefficients, as well as the velocity and temperature profiles, are presented and discussed. Originality/value: Dual solutions for the opposing flow and multiple solutions for the assisting flow are found.